2018
DOI: 10.1002/jcb.27934
|View full text |Cite
|
Sign up to set email alerts
|

The effect of VDR gene polymorphisms and vitamin D level on blood pressure, risk of preeclampsia, gestational age, and body mass index

Abstract: We investigated the influence of vitamin D receptor (VDR) polymorphisms and vitamin D level on the blood pressure and the risk of preeclampsia. In a case‐control study, 200 pregnant women, including 100 individuals with preeclampsia along with 100 healthy pregnant women, were studied for VDR FokI, TaqI, and BmsI polymorphisms and serum 25 (OH)‐D level using polymerase chain reaction‐restriction fragment length polymorphism method and commercial kit, respectively. The mean level of 25 (OH)‐D in preeclamptic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…The C allele of VDR FokI polymorphism does not have the rst ATG, and translation starts at the second ATG. So, the presence of this allele producing a shorter VDR protein by 3 amino acids compared with the T allele (10). In the present study, signi cantly higher frequency of the FokI C allele was detected in SS and S/β thal patients than controls.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The C allele of VDR FokI polymorphism does not have the rst ATG, and translation starts at the second ATG. So, the presence of this allele producing a shorter VDR protein by 3 amino acids compared with the T allele (10). In the present study, signi cantly higher frequency of the FokI C allele was detected in SS and S/β thal patients than controls.…”
Section: Discussionsupporting
confidence: 51%
“…The phenol-chloroform method was used for the extraction of DNA from the leukocyte of the EDTA-treated whole blood (9). The FokI T>C (rs2228570) in exon 2 and the TaqI T>C (rs731236) in exon 9 of the VDR gene were detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method as previously described (10). The GC rs7041 was identi ed by the PCR-RFLP method using the HaeIII restriction enzyme (7).…”
Section: Genotypingmentioning
confidence: 99%
“…That PE is characterized by defective placentation at early stages of pregnancy and that hypovitaminosis D is frequently found in women with PE, suggest a potential role for vitamin D as a crucial molecule in normal placentation. An association between VDR FokI polymorphism and the risk of PE has also been reported, suggesting that the interaction of vitamin D with its receptor is required for placenta development and function (139). It has also been suggested that low levels of vitamin D may disrupt the immune balance leading to overexpression of Th1 cytokines and failure of immunological tolerance toward embryo implantation (133).…”
Section: The Role Of Vitamin D In Pregnancy: From Conception To Partumentioning
confidence: 99%
“…Our observations are similar with those recently reported by Rezavand and co-workers, showing that a significantly higher frequency of VDR FokI F allele is observed in preeclamptic patients (83%) than in controls (74%) and is associated with a 1.72-fold increased risk of PE. In particular, the FokI FF genotype resulted to be associated with a significantly higher blood pressure when compared to fF and ff +fF genotypes [40].…”
Section: Plos Onementioning
confidence: 88%